Transgenerational evaluation of Elateriospermum tapos extracts on the male offspring of obesity-induced sprague dawley rats - Santhra Segaran Balan,; Azrina Zainal Abidin,; Kokila Vani Perumal,; Nurul Husna Shafie,; Maizaton Atmadini Abdullah,; Azmiza Syawani Jasni,; Kwaifa, Ibrahim Kalle; Hasnah Bahari, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Obesity has been considered as a great public health concern, that has spread in both economic and poor resources countries. This study aimed to investigate the effect of Elateriospermum tapos supplementation on the male offspring of female obesity-induced Sprague Dawley (SD) rats at weaning and adult age. A total of thirty (30) female and fifteen (15) male Sprague Dawley rats (N=45) were purchased for this study. Of the 30 female rats, six (n=6) were randomly selected as the control group (CG) and fed separately with male on standard chow diet, while the remaining rats (n=24) were fed on a high-fat diet for 5 weeks. The obese group were further randomly divided into 4 groups, positive control group (PG), orlistat treatment (DG) at 200 mg/kg, treatment 1 (TX1, 200 mg/kg E. tapos seed) and treatment 2 (TX2, 200 mg/kg E. tapos shell) for 6 weeks. One male pup from each dam was culled at weaning (postnatal day 21 (PND21)) and adulthood (12 weeks). The liver, kidney, retroperitoneal white adipose tissue (RpWAT) and brown adipose tissue (BAT) were collected for histopathological study. Serum lipid profiles, liver enzyme activities and creatinine were measured. The bodyweight of male offspring from treatment 1 (MTX1) and 2 (MTX2) was significantly lower (P<0.05) compare to MNG group. The RpWAT weight in MTX1 and MTX2 for adult offspring also were significantly lower (P<0.05) compared to MPG. The histopathological examination of liver in MCG, MDG, MTX1, and MTX2 showed normal hepatocytes while the MPG group showed the presence of ballooning cell and hypertrophy of adipocytes was also observed in MPG group compared to another group’s rat. The E. tapos extracts from the shell have greater therapeutic potential on maternal obesity in short and long term treatment.